Transcutaneous Electrical Nerve Stimulation on the PC-5 and PC-6 Points Alleviated Hypotension after Epidural Anaesthesia, Depending on the Stimulus Frequency. (31st January 2012) - Arai, Young-Chang P.; Ito, Akihiro; Ohshima, Kenji; Hibino, Soki; Niwa, Sinnosuke; Kawanishi, Jun; Numanami, Hiroki; Sakakima, Yoshikazu; Mizuno, Shouji; Tawada, Yusuke; Maruyama, Yuki; Sato, Jun; et al.
Abstract : Neuraxial blockade causes arterial hypotension. Transcutaneous electrical nerve stimulation (TENS) at the Neiguan (PC-6) and Jianshi (PC-5) reduces the severity of hypotension after spinal anaesthesia, but did not clarify the optimal stimulus frequency. We hypothesized that the stimulus frequency of TENS at the PC-6 and PC-5 points would influence the severity of hypotension after epidural anaesthesia. 65 ASA I or II male patients presenting for inguinal hernia repair were randomized to five groups: the control group received no treatment; the 2 Hz, 10 Hz, 20 Hz, and 40 Hz groups received TENS at a frequency of 2 Hz, 10 Hz, 20 Hz, and 40 Hz, respectively. The lowest SBP was significantly higher in the 40 Hz group [the control, 84 (74–110) mmHg; the 2 Hz, 96 (62–116) mmHg; the 10 Hz, 100 (68–110) mmHg; the 20 Hz, 96 (64–115) mmHg; the 40 Hz, 104 (75–140) mmHg: P = 0.004 ]. Significantly less patients experienced hypotension in the 40 Hz group [the control, 78%; the 2 Hz, 43%; the 10 Hz, 38%; the 20 Hz, 38%; the 40 Hz, 8%: P = 0.008 ]. TENS on the PC-6 and PC-5 points reduced the severity and incidence of hypotension after epidural anaesthesia, depending on the stimulus frequency.